Medulloblastomics: the end of the beginning - Northcott, Paul A.; Jones, David T. W.; Kool, Marcel; Korshunov, Andrey; Lichter, Peter; Pfister, Stefan (Nature reviews. Cancer, 2012)
The division of medulloblastoma into different subgroups by microarray expression profiling has dramatically changed our perspective of this malignant childhood brain tumour. Now, the availability of next-generation sequencing and complementary high-density genomic technologies has unmasked novel driver mutations in each medulloblastoma subgroup. The implications of these findings for the management of patients are readily apparent, pinpointing previously unappreciated diagnostic and therapeutic targets. In this Review, we summarize the 'explosion' of data emerging from the application of modern genomics to medulloblastoma, and in particular the recurrent targets of mutation in medulloblastoma subgroups. These data are currently making their way into clinical trials as we seek to integrate conventional and molecularly targeted therapies.